A supervisory control strategy for series hybrid electric vehicles with two energy storage systems - Pisu, P.; Rizzoni, G. (2005 IEEE Vehicle Power and Propulsion Conference, 2005)
Regardless of the topology of the hybrid electric vehicle, the essence of the HEV control problem is the instantaneous management of the power flows from the various energy storage devices to achieve the overall control objectives. In this paper we consider the case of energy management for a series hybrid powertrain configuration with two energy storage systems, i.e. batteries and ultracapacitors. The proposed power split algorithm is based on a modified instantaneous equivalent consumption minimization strategy (ECMS). The methodology could easily be applied to any kind of powertrain subject to the charge-sustaining constraint, and can readily be adapted to the specific characteristics of the components used in the powertrain.